Effects of human serum and apo‐Transferrin on Staphylococcus epidermidis RP62A biofilm formation. Issue 6 (16th May 2016) - She, Pengfei; Chen, Lihua; Qi, Yong; Xu, Huan; Liu, Yuan; Wang, Yangxia; Luo, Zhen; Wu, Yong
Abstract: Biofilm‐associated Staphylococcus epidermidis infections present clinically important features due to their high levels of resistance to traditional antibiotics. As a part of human innate immune system, serum shows different degrees of protection against systemic S. epidermidis infection. We investigated the ability of human serum as well as serum component to inhibit the formation of, and eradication of mature S. epidermidis biofilms. In addition, the synergistic effect of vancomycin combined with apo‐Transferrin was checked. Human serum exhibited significant antibiofilm activities against S. epidermidis at the concentration without affecting planktonic cell growth. However, there was no effect of human serum on established biofilms. By component separation, we observed that antibiofilm effect of serum components mainly due to the proteins could be damaged by heat inactivation (e.g., complement) or heat‐stable proteins ≥100 kDa. In addition, serum apo‐Transferrin showed modest antibiofilm effect, but without influence on S. epidermidis initial adhesion. And there was a synergistic antibiofilm interaction between vancomycin and apo‐Transferrin against S. epidermidis . Our results indicate that serum or its components (heat‐inactivated components or heat‐stable proteins ≥100 kDa) could inhibits S. epidermidis biofilm formation. Besides, apo‐Transferrin could partially reduce the biofilm formation at the concentration that does not inhibit planktonic cell growth. Abstract : Human serum inhibits Staphylococcus epidermidis biofilm formation, and this is mainly due to the complement and serum proteins at the size more than 100 kDa; apo‐Transferrin could partially reduce the biofilm formation at the concentration that do not inhibit planktonic cell growth.